Avaliação do diagnóstico do desempenho dos alunos do ensino médio na olimpíada tocantinense de química: - Silva, Lívia Fernandes da (Universidade Federal do Tocantins, 2023)
This paper addresses the prospective study to evaluate the learning development of the Tocantins high school students about the perception of curricular programmatic content, in face of the answers to the problem questions of exams from the Tocantins and Chemistry Olympiad (OTQ) in 2015. It also seeks to relate this degree of knowledge with their possible causes. The study was conducted in order to check whether or not there is a higher student learning in specific content and how this knowledge is effective in a summative evaluation. They were analyzed all exam questions of OTQ with their respective contents. Investigations to present content on selected items had as propose to analyze the performance and epistemological knowledge of students. With the results could be seen that the performance of the public network was more inferior than private schools in all the years and the evolution of the learning of contents was more uneven in the public network demonstrating discontinuity in the understanding of the content.